Estuarine ecological risk based on hepatic histopathological indices from laboratory and in situ tested fish - Costa, P. M. (2021)
Juvenile Senegalese soles were exposed through 28-day laboratory and field (in situ) bioassays to sediments from three sites of the Sado estuary (W Portugal): a reference and two contaminated by metallic and organic contaminants. Fish were surveyed for ten hepatic histopathological alterations divided by four distinct reaction patterns and integrated through the estimation of individual histopathological condition indices. Fish exposed to contaminated sediments sustained more damage, with especial respect to regressive changes like necrosis. However, differences were observed between laboratory- and fieldexposed animals, with the latest, for instance, exhibiting more pronounced fatty degeneration and hepatocellular eosinophilic alteration. Also, some lesions in fish exposed to the reference sediment indicate that in both assays unaccounted variables produced experimental background noise, such as hyaline degeneration in laboratory-exposed fish. Still, the field assays yielded results that were found to better reflect the overall levels of contaminants and physico-chemical characteristics of the tested sediments.